Comparative Candidates Survey (CCS) Module II - Cumulative Dataset 2013 - 2018 - Lutz, Georg; Tresch, Anke (2022)
The Comparative Candidates Survey (CCS) is a response to the growing number of candidate surveys in the Anglo-saxon world and beyond. The rational of the CCS is to harmonise these dispersed efforts and give them a cross-nationally comparable core. The CCS is an internationally coordinated effort. It combines an internationally agreed and locally adapted core questionnaire with questions that try to capture national and election specifics. The core candidate questionnaire specifically focuses on the issue of individualisation of electoral campaigns, i.e. the empirical question to what extent the candidates run their own campaigns distinct from those of their parties. CCS has been running since 2005. Using the CCS Module I questionnaire, the first wave includes candidate surveys from 32 elections across 24 countries. The second wave incorporates candidate surveys from 30 parliamentary elections in 21 countries, where the CCS Module II questionnaire was used. To date, the third wave contains candidate surveys from 5 elections across 5 countries that used the CCS Module III questionnaire. More information on the project can be found on the CCS website (www.comparativecandidates.org).